Advances in the use of nanomaterials for nucleic acid detection in point-of-care testing devices: A review - He, Ziyu; Liu, Changsheng; Li, Zhongyu; Chu, Zhou; Chen, Xiang; Chen, Xupeng; Guo, Yuan (Frontiers in Bioengineering and Biotechnology, 2022)
The outbreak of the coronavirus (COVID-19) has heightened awareness of the importance of quick and easy testing. The convenience, speed, and timely results from point-of-care testing (POCT) in all vitro diagnostic devices has drawn the strong interest of researchers. However, there are still many challenges in the development of POCT devices, such as the pretreatment of samples, detection sensitivity, specificity, and so on. It is anticipated that the unique properties of nanomaterials, e.g., their magnetic, optical, thermal, and electrically conductive features, will address the deficiencies that currently exist in POCT devices. In this review, we mainly analyze the work processes of POCT devices, especially in nucleic acid detection, and summarize how novel nanomaterials used in various aspects of POCT products can improve performance, with the ultimate aims of offering new ideas for the application of nanomaterials and the overall development of POCT devices.